Gerakan Konservasi Wonorejo Surabaya mangrove forest conservation movement from 1998 to 2011 - Nasifatul Hasanah (Historia, 2020)
ABSTRACT This article examines the Wonorejo Rungkut mangrove forest conservation movement in Surabaya from 1998-2011. The purpose of this study is to discuss the background of the Wonorejo mangrove forest conservation movement from 1998-2011 and the impact of the mangrove forest conservation movement. The method used in this study is the historical method with heuristic stages, source criticism, interpretation, and historiography. The discussion is based on primary sources in the form of interviews with parties deemed to know and master matters related to the Wonorejo mangrove forest conservation movement and reinforced with relevant secondary sources. It was concluded that the movement of mangrove forest conservation was motivated by the existence of illegal logging and the lack of public awareness of the mangrove forest area so that the mangrove forest area was converted into a residential development area. The Wonorejo mangrove forest conservation movement was pioneered by two figures, namely Soni Mohson and Lulut Sri Yuliani. The two groups moved the Wonorejocommunity to care about the mangrove forest. The mangrove forest conservation movement that lasted 14 years had a positive impact in the from of the emergence of processed mangrove products. Keywords: Conservation movement, mangrove forest, Wonorejo